THE FUNCTION OF ENVIRONMENTAL LAW IN ACADEMIC CONTEXT: ENVIRONMENTAL LAW LITERACY - Tamaulina Br Sembiring; Marjan Miharja; Irma Rachmawati Maruf; Endang Fatmawati (ADISAM Publisher, 2022)
The function and existence of environmental Law certainly have an essential role in solving the problem of environmental damage in Indonesia, which has been claimed to be one of the countries that have failed to manage environmental management. Based on this interest, we try to review the Law and the function of environmental Law in an academic context in the hope of obtaining findings from various theoretical and application contexts. In reviewing various sources, we involve a comprehensive data coding system, in-depth data evaluation, and interpretations where we believe it is relevant to answer high facilities' problems. Our data search online on several publications released between 2010 and 2022 considering the last ten years, the issue of damage and the government's efforts to salvage support is increasing. It is hoped that this finding will be a refinement of further studies. At the same time, the purpose of this study is to collect several facts in the form of scientific evidence related to the function of environmental Law in an academic context.